Tinjauan Kritis Terhadap Kebijakan Pengaturan Masalah Pidana Dan Pemidanaan Dalam RUU KUHP - Rusli Muhammad (Jurnal Hukum IUS QUIA IUSTUM, 2006)
The tendency of criminal regulation and punishment in the Criminai Cocfe Draft more emphasize to the relative theory than other theories. Nevertheless, the imprisonment sanction still becomes the priority, and the great sanction is imposed to the crime appointed to the state which is greater than crime to the religion.